Development of a rapid and simple LC-MS/MS method for identification and quality control of natural Calculus bovis and Calculus bovis sativus. Issue 18 (21st September 2015) - Feng, Chengyang; Li, Xiping; Zhang, Chengliang; He, Guangzhao; Xu, Yanjiao; Li, Wei; Yu, Zaoqin; Cai, Hongjiao; Liu, Dong
<x xml:space="preserve">Abstract</x> Calculus bovis sativus (C. bovis sativus, CBS), with the same pharmacodynamics activities as those of natural C. bovis (CB), has been approved as an ideal substitute in China.